Dom-chromatic Number of certain graphs - Usha, P; Punitha, Joice M; Angeline, Beulah EF (International Journal of Computer Sciences and Engineering, 2025)
For a given -coloring of a graph , a dominating set is said to be dom-colouring set if it contains at least one vertex from each colour class of G. The dom-chromatic number is the minimal cardinality taken over all domcolouring sets and is denoted by . In this paper we have obtained the dom-chromatic number of various types of graphs like star graphs, windmill graphs, ladder graphs, comb graphs and for cycles